2019
DOI: 10.1177/1971400919881464
|View full text |Cite
|
Sign up to set email alerts
|

Refractory seizures: Prediction of outcome of surgical intervention based on results from PET-CT, PET-MRI and electroencephaolography

Abstract: Purpose The purpose of this article is to evaluate the effectiveness of fluorodeoxyglucose (FDG) positron emission tomography (PET)-computed tomography (CT) and PET-magnetic resonance imaging (MRI) with scalp and intracranial electroencephalogram (EEG) in predicting surgical outcomes in patients with refractory seizures. Methods Patients who underwent PET-CT and MRI fusion, scalp and intracranial EEG, and subsequent surgical intervention were retrospectively included. PET-CT were fused with MRI and interpreted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…This finding further confirmed that multimodal imaging, as an independent complementary method that supplements the clinical information, has a significant value in pre-surgical evaluation and the prediction of post-surgical prognosis. The present results were partially consistent with those of Johnson et al 30 Two patients in the concordant group of the present study had poor outcomes because the resection range was smaller than the pre-surgical lesion range, and brain tissue gliosis was found around the operative area (Fig 4). Two patients in the discordant group (unilateral image abnormality with bilateral v-EEG abnormalities) had favourable outcomes, which might be related to the rapid diffusion of abnormal discharges.…”
Section: Discussionsupporting
confidence: 93%
“…This finding further confirmed that multimodal imaging, as an independent complementary method that supplements the clinical information, has a significant value in pre-surgical evaluation and the prediction of post-surgical prognosis. The present results were partially consistent with those of Johnson et al 30 Two patients in the concordant group of the present study had poor outcomes because the resection range was smaller than the pre-surgical lesion range, and brain tissue gliosis was found around the operative area (Fig 4). Two patients in the discordant group (unilateral image abnormality with bilateral v-EEG abnormalities) had favourable outcomes, which might be related to the rapid diffusion of abnormal discharges.…”
Section: Discussionsupporting
confidence: 93%
“…Hybrid PET/MRI In clinical practice, PET could serve as a complementary presurgical examination to EEG for SOZ identification. Johnson et al (2020) revealed that concordance of SOZ localization between PET and EEG was associated with favorable surgical outcomes in almost all patients while discordance had equal chance of favorable or unfavorable outcomes. According to Desarnaud et al (2018) the localization rate of SOZs was 83% after integration of electroclinical data and PET/MRI in patients with pathologically proven focal cortical dysplasia type 2 (FCD2), significantly higher than that of PET or EEG alone.…”
Section: Discussionmentioning
confidence: 96%
“…4,9 However, in adults with temporal lobe epilepsy, volume reduction in the hippocampus has been shown to correlate with the duration of epilepsy. [10][11][12] Most studies that have assessed hippocampal volumes in children with epilepsy have evaluated total or regional hippocampal volume; that is, hippocampal head, body and tail, and have been cross-sectional in design. [4][5][6]8,11,13,14 Hence, it is uncertain if hippocampal volumes decline over time with ongoing seizures.…”
Section: Introductionmentioning
confidence: 99%